Review: Extensive Potentiality of Selected Tropical Fruits from Indonesia - Andriati Ningrum; Matthias Schreiner (Indonesian Food and Nutrition Progress, 2017)
Indonesia has several biodiversities including tropical fruits.   The consumption of tropical fruits is increasing as this source can be used as a healthy source of several bioactive compounds to prevent severalnon-communicable diseases.  Tropical fruits are commonly used for the production of several food products e.g. juice, jams, jellies, cookies and other products.  The utilization of by product of tropical fruits have not been developed and promoted.  Although, several bioactive compounds are still present in tropical fruits by product.  This concept called as avalorization of by product to increase the economical value of several by product.  The purpose of this review isto promote several selected Indonesian tropical fruit and also to promote the potency of a by-product of tropical fruits in valorization concept.